Proposing A Practical Accounting Procedure for Al-Kautsar II Islamic Kindergarten - Febriani, Arianti (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2024)
This study aims to analyze the application of the cash receipt and expenditure cycle at Al-Kautsar II Islamic Kindergarten, Pondok Gede. In addition, this study also aims to compile proposals for the implementation of Standard Operating Procedures (SOPs) in the cash receipt and expenditure cycle at Al-Kautsar II Islamic Kindergarten, Pondok Gede. The object of this study is Al-Kautsar II Islamic Kindergarten. Al-Kautsar II Islamic Kindergarten is one of the kindergartens located in Pondok Gede, Bekasi. This research uses a development research (R&D) approach by adopting ADDIE as its development model. The ADDIE model only applies three phases, namely analysis, design, and development. This study used primary data generated from interviews with kindergarten administrators, while secondary data obtained from supporting documents owned by kindergarten administrators. Data analysis methods are carried out using data reduction techniques, data presentation, and conclusions.